Interacting cracks 3D analysis using boundary integral equation method - Bohdan Stasyuk (AIMS Materials Science, 2016)
This paper presents a modification of the method of boundary integral equations suitable for the efficient solution of 3D problems on the arbitrarily oriented plane cracks interaction with the influence of body surface. The hypersingular boundary integral equations on the crack-surface are transformed into new form, where the solution behavior near the crack front is accounted implicitly. This modification allows the direct determination of the stress intensity factors (SIF) in the crack vicinity after solution of equations by the collocation technique. We also propose the approach based on the determination of the effective stress field formed in the vicinity of a fixed crack by neighboring cracks interacting with this crack and with boundary surface. Numerical examples concern an asymmetric problem for interacting penny-shaped plane cracks in the unlimited and limited bodies. The reliability of the results obtained by the method of effective stress field is checked by comparing with the exact solution of the problem of interaction of two penny-shaped cracks.